Protoporphyrin IX Extraction from Quail Eggshell (Cortunix cortunix) and Its Complexity with Zn(II) - A. Rindang Anggit Laksono; Yohanes Martono; Cucun Alep Riyanto (EKSAKTA: Journal of Sciences and Data Analysis, 2018)
The aim of this research is to find the optimal condition for  Zn(II) complexation with protoporphyrin IX which is a natural coloring pigment on quail eggshell. The concentration of protoporphyrin IX extract is  0.01% (w / w) of the dried extract. The results of the complex are analyzed using Response Surface Methodology (RSM). The design used was central composite design with 3 factor variables X1 = pH (2; 4; 6), X2 = ratios (1: 3,1: 4,1: 5) and X3 = time (30 ', 60', 90 '). The modeling used is linear and shows that the pH, ratio, and time factor have an influence on the complexation. This model gives the absorbance equation Y = 2.12506 - 0.049856X1 - 020316X2 - 0,00409857X3 and gives treatment in the most optimum complexation of pH 2; ratio of 1: 3; and time for 30 minutes with the absorbance of 1,293 and the desirability value of 0.825.